2021
DOI: 10.1093/jmt/thab010
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Recruiting People With Dementia to Music Therapy Studies: Systematic Review

Abstract: Positive effects of music therapy for people with dementia and their family carers are reported in a growing number of studies. However, small sample sizes or low recruitment rates often limit the success of these research studies. More adequately powered evidence-based studies are needed to impact policy and funding in dementia care. This systematic review examined recruitment strategies in music therapy clinical trials involving people living with dementia and/or their family carers. Eligible studies describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Small sample sizes or low recruitment rates often limit the success of comparable research studies ( 58 ), approximately 50% of clinical trials fall short of reaching their recruitment targets ( 59 ). Results of a recent review from Baker et al ( 58 ), with the aim of researching the percentage of music therapy studies of people living with dementia met their target sample size, showed that only one study from the 14 studies reviewed (music therapy delivered in people with dementia living in nursing homes) reached 89% of its target sample size. Only five studies had a RCT design and only one study had a sample size over 100 ( N = 117).…”
Section: Discussionmentioning
confidence: 99%
“…Small sample sizes or low recruitment rates often limit the success of comparable research studies ( 58 ), approximately 50% of clinical trials fall short of reaching their recruitment targets ( 59 ). Results of a recent review from Baker et al ( 58 ), with the aim of researching the percentage of music therapy studies of people living with dementia met their target sample size, showed that only one study from the 14 studies reviewed (music therapy delivered in people with dementia living in nursing homes) reached 89% of its target sample size. Only five studies had a RCT design and only one study had a sample size over 100 ( N = 117).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, four main music-based interventions are commonly distinguished in therapeutic practice, which may overlap or be mixed, namely, music-based activities, such as choir singing or drumming, that include improvising, listening, recreating, and composing ( Stegemann et al, 2019 ). Previous studies have proved that music therapy can be applied to the clinical practice of various neurological and psychiatric disorders ( Boso et al, 2006 ; Baker et al, 2021 ). Furthermore, combined physical activity and music interventions produce considerable benefits for patients with AD, including improved heart rates, skin conductance, motor patterns, neuroendocrine response, and immunological functions ( Ooishi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%